2016
DOI: 10.18632/oncotarget.11761
|View full text |Cite
|
Sign up to set email alerts
|

Leptin promotes migration and invasion of breast cancer cells by stimulating IL-8 production in M2 macrophages

Abstract: This study aims to investigate the mechanisms underlying leptin-mediated crosstalk between tumor-associated macrophages (M2 macrophages) and breast cancer cells. THP1 human leukemic monocytes were induced to differentiate into M2 macrophages by PMA (100 nM) and IL-4 (20 ng/mL). Quantitative RT-PCR and Western blot revealed that leptin (100 nM) significantly increased the expression of leptin receptor (ObR) in the M2 macrophages (P < 0.01) and stimulated interleukin (IL)-8 expression in the M2 macrophages, mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
2
48
0
2
Order By: Relevance
“…Fascinatingly, TAMs have been considered as M2 macrophages, which could promote the EMT [145–147]. A recent study has shown that leptin may promote breast cancer progression by stimulating M2 macrophages [148]. Using a different approach Strong et al [11] co-cultured adipose stromal/stem cells isolated from obese women with either ER+ MCF-7, ZR75, or T47D human breast cancer cells, which resulted in enhanced expression of EMT and metastasis related genes, SERPINE1, MMP-2, and IL-6.…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Fascinatingly, TAMs have been considered as M2 macrophages, which could promote the EMT [145–147]. A recent study has shown that leptin may promote breast cancer progression by stimulating M2 macrophages [148]. Using a different approach Strong et al [11] co-cultured adipose stromal/stem cells isolated from obese women with either ER+ MCF-7, ZR75, or T47D human breast cancer cells, which resulted in enhanced expression of EMT and metastasis related genes, SERPINE1, MMP-2, and IL-6.…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
“…Some of the well-studied signaling pathways/molecules include: MAPK/ERK, PI3K/AKT, STAT, TGF-β, and Wnt/β-Catenin [205]. Fascinatingly, many of these molecules are linked with the signal transduction pathways of leptin (Table 4 [14,108,109,113,118,120,129,142,144,148,152,153,206222]).…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that inflammation is involved in almost all tumor processes. Notably, leptin, in addition to its direct effects on breast cancer epithelial cells, has been demonstrated to stimulate the function of macrophages, one of the most abundant and critical immune cell types within the breast tumor microenvironment [22,[50][51][52]. Thus, we investigated whether an enhanced production of leptin from AnaR cells may impact the macrophage phenotype to support malignant progression further.…”
Section: Enhanced Recruitment and Protumor Activation Of Macrophagesmentioning
confidence: 99%
“…Its tumorigenic action is mediated by JAK/STAT, PI3K/PTEN/Akt/mTOR, Raf/MER/ERK pathways [20, 21]. Serum leptin has been detected in various cancers with conflicting results.…”
Section: Introductionmentioning
confidence: 99%